Klebsiella pneumoniae producing bacterial toxin colibactin as a risk of colorectal cancer development - A systematic review - Strakova, Nicol; Korena, Kristyna; Karpiskova, Renata (Toxicon (Oxford), 2021)
Microbiota can significantly contribute to colorectal cancer initiation and development. It was described that E. coli harbouring polyketide synthase (pks) genes can synthetize bacterial toxin colibactin, which was first described by Nougayrede's group in 2006. E. coli positive for pks genes were overrepresented in colorectal cancer biopsies and, therefore, prevalence and the effect of pks positive bacteria as a risk factor in colorectal cancer development is in our interest. Interestingly, pks gene cluster in E. coli shares a striking 100% sequence identity with K. pneumoniae, suggesting that their function and regulation are conserved. Moreover, K. pneumoniae can express a variety of virulence factors, including capsules, siderophores, iron-scavenging systems, adhesins and endotoxins. It was reported that pks cluster and thereby colibactin is also related to the hypervirulence of K. pneumoniae. Acquisition of the pks locus is associated with K. pneumoniae gut colonisation and mucosal invasion. Colibactin also increases the likelihood of serious complications of bacterial infections, such as development of meningitis and potentially tumorigenesis. Even though K. pneumoniae is undoubtedly a gut colonizer, the role of pks positive K. pneumoniae in GIT has not yet been investigated. It seems that CRC-distinctive microbiota is already present in the early stages of cancer development and, therefore, microbiome analysis could help to discover the early stages of cancer, which are crucial for effectiveness of anticancer therapy. We hypothesize, that pks positive K. pneumoniae can be a potential biomarker of tumour prevalence and anticancer therapy response. [Display omitted] •pks positive E.coli producing colibactin are suspected to contribute to initiation and development of colorectal cancer.•Human gut is often a reservoir of K. pneumoniae.•K. pneumoniae can express a variety of virulence factors, including toxin colibactin.•Detection of colibactin by DNA adducts, side product (N-myristoyl-D-asparagine) and by colibactin gene expression.•pks positive K. pneumoniae may be a potential biomarker of tumour prevalence and anticancer therapy response.